2013
DOI: 10.1371/journal.pone.0055939
|View full text |Cite
|
Sign up to set email alerts
|

Complex Responses of Intertidal Molluscan Embryos to a Warming and Acidifying Ocean in the Presence of UV Radiation

Abstract: Climate change and ocean acidification will expose marine organisms to synchronous multiple stressors, with early life stages being potentially most vulnerable to changing environmental conditions. We simultaneously exposed encapsulated molluscan embryos to three abiotic stressors—acidified conditions, elevated temperate, and solar UV radiation in large outdoor water tables in a multifactorial design. Solar UV radiation was modified with plastic filters, while levels of the other factors reflected IPCC predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
1
35
0
1
Order By: Relevance
“…The prevailing additive nature of their joint effects implies that warming tended to compensate for the negative effects of UV‐B radiation. For instance, we found that warming alleviated the negative effect of UV‐B radiation on marine organisms' fitness and the performance of marine larvae (Figure ), as warming generally enhanced metabolic processes that were suppressed by UV‐B (Davis et al, ; Li, Gao, Villafane, & Helbling, ; Moresino & Helbling, ; Vidussi et al, ). The compensatory effects of warming on the negative effects of elevated UV‐B radiation could be partly explained by temperature‐dependent photoenzymatic repair (PER), which is an enzyme‐mediated process and therefore tends to increase with increasing temperature (Langenbacher et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…The prevailing additive nature of their joint effects implies that warming tended to compensate for the negative effects of UV‐B radiation. For instance, we found that warming alleviated the negative effect of UV‐B radiation on marine organisms' fitness and the performance of marine larvae (Figure ), as warming generally enhanced metabolic processes that were suppressed by UV‐B (Davis et al, ; Li, Gao, Villafane, & Helbling, ; Moresino & Helbling, ; Vidussi et al, ). The compensatory effects of warming on the negative effects of elevated UV‐B radiation could be partly explained by temperature‐dependent photoenzymatic repair (PER), which is an enzyme‐mediated process and therefore tends to increase with increasing temperature (Langenbacher et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Overall, both molluscs and echinoderms seem equally vulnerable to ocean acidification at premetamorphic stages (Fig. 6) (Parker et al, 2010;Byrne et al, 2011), although intertidal and infaunal species may show increased resilience due to adaptation to pH fluctuations in rock pools (Davis et al, 2013) or low pH in sediments (Talmage & Gobler, 2011;Styf et al, 2013;Nguyen & Byrne, 2014). The impacts of acidification on calcification on echinoderms appear largely due to metabolic change (Byrne et al, 2013a;Evans et al, 2014) and less so to their vulnerable high magnesium calcite skeleton (Andersson et al, 2008).…”
Section: Vulnerable and Resilient Taxamentioning
confidence: 99%
“…An understanding of physiology may help explain complex responses to multiple stressors (e.g. Davis et al, 2013), as has been shown in the variation in the metabolic responses of amphipods . In addition, physiological investigations will help increase the taxonomic resolution of predictions of impact.…”
Section: Future Directions and Recommendationsmentioning
confidence: 99%
“…responses under ocean acidification of Aplysia or any other sea hare species (the clade Anaspidea); low pH was shown to increase mortality in the embryos of a tropical sea hare (Davis et al, 2013). One additional study found increased respiratory pumping in Aplysia californica in seawater into which CO 2 was bubbled, causing extreme and rapid hypercapnia (a decrease to 5.9 pH over 10 min ;Croll, 1985).…”
Section: Discussionmentioning
confidence: 99%